Discordance between Criteria-diagnosed and clinically-diagnosed Asthma COPD Overlap (ACO) among hospitalized patients in an Indian referral hospital. - Daniel, Jefferson; Isaac, Barney; Christopher, Devasahayam Jesudas (Eastern Journal of Medical Sciences, 2023)
Background and Objectives: Asthma-COPD-overlap (ACO), as a single entity, has been widely contested over the past few years. Most ACO diagnostic criteria do not agree with each other when applied to respiratory patients. From 2016 to 2020, GINA described a syndromic approach for diagnosing ACO, which was replaced with a broader approach after 2021. We intended to learn if the GINA criteria and the CSMA Screening tool agreed with a clinical diagnosis of ACO. Methods: We performed a retrospective cross-sectional analysis of inpatients with a clinical diagnosis of ACO from 2014 to 2019. We reclassified these patients into Not-ACO and ACO using the GINA syndromic approach 2019 (GSA 2019), Modified GINA syndromic approach 2019 (MGSA 2019), GINA 2021 and the CSMA tool. We used Kappa statistics to compare the performance of various tools. Results: 83 clinically diagnosed ACO patients were included. According to GINA syndromic approach 2019, only 41 (49.39%) patients would be classified as ACO. GINA 2021 picked up 57 (68.67%) patients as ACO. The modified GINA syndromic approach 2019, which we proposed, identified 67 (80.72%) patients as ACO. The CSMA tool identified 63 (75.90%) patients as ACO. The GINA 2019 criteria, when interpreted liberally as described by us, have a better agreement with the CSMA tool with a sensitivity of 87.3% and specificity of 40%, with a ’k’ agreement of 29.3%. Conclusion: The standard GINA syndromic approach 2019 Tool is stringent and may sometimes miss the ACO diagnosis. The original GINA syndromic approach table 2019 should be brought back with modifications.